2016
DOI: 10.1021/acs.jpcc.6b11253
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of ZnCr2S4 Spinel under Pressure

Abstract: The series of Cr-chalcogenide spinels ACr 2 X 4 (A = Zn, Cd, Hg; X = S, Se) exhibits a rich phase diagram upon compression, as revealed by our recent investigations. There exist, however, some open questions regarding the role of cations in the observed structural transitions. In order to address these queries, we have performed X-ray diffraction and Raman spectroscopic studies on the ZnCr 2 S 4 spinel up to 42 GPa, chosen mainly due to the similarity of the Zn 2+ and Cr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…The errors in the fitting results come from the fitting process without including the propagation of uncertainties from pressure and volume. The bulk modulus of the cubic phase of this lacunar spinel compound is different from other conventional spinels, such as ZnGa 2 O 4 , ZnCr 2 Se 4 , CoCr 2 O 4 , CuCr 2 O 4 , ZnCr 2 S 4 , MnCr 2 O 4 , NiCr 2 O 4 , CdCr 2 Se 4 , and so on. The discrepancies are predominantly caused by the different crystal structures, F 4̅3 m versus Fd 3̅ m , in these two systems.…”
Section: Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The errors in the fitting results come from the fitting process without including the propagation of uncertainties from pressure and volume. The bulk modulus of the cubic phase of this lacunar spinel compound is different from other conventional spinels, such as ZnGa 2 O 4 , ZnCr 2 Se 4 , CoCr 2 O 4 , CuCr 2 O 4 , ZnCr 2 S 4 , MnCr 2 O 4 , NiCr 2 O 4 , CdCr 2 Se 4 , and so on. The discrepancies are predominantly caused by the different crystal structures, F 4̅3 m versus Fd 3̅ m , in these two systems.…”
Section: Results and Discussionmentioning
confidence: 74%
“…Like temperature, pressure is another controllable variable that can be externally altered to tune and probe the physical natures (lattice structure, optical, and electrical properties) of GaV 4 S 8 due to the strong coupling between lattice, electronic, and spin degrees of freedom in this compound . More interesting, whether the Jahn–Teller effect, which has been observed in GaV 4 S 8 at the cooling condition as well as in CuWO 4 , MnCr 2 O 4 , NiCr 2 O 4 , and ZnCr 2 S 4 under high pressure, is enabled to be induced by compression at room temperature in this compound. However, the literature gives very limited information about the high-pressure behavior of GaV 4 S 8 ; , Even its crystal structure transformation under room temperature compression is unknown. In the present study, we used high-pressure synchrotron single crystal and powder X-ray diffraction to detect the delicate change in the crystal structure of this material under a broad pressure range from ambient to 60 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…from the starting FM states towards AFM ones [20][21][22] . Taken together, we were able to identify a linear relationship between the P Tr of Crbearing spinel sulfides and selenides and the K nnn /J nn ratio of next-nearest neighbor K nnn to nearest neighbor J nn Cr 3+ magnetic exchange interactions 19,20 .…”
Section: Pressure-induced Structural Transition and Magnetic Exchamentioning
confidence: 76%
“…In previous works we have unraveled the close correlation between the magnetic exchange interactions and the pressure-induced structural transitions in ACr 2 X 4 Cr-spinel chalcogenides with non-magnetic A 2+ cations (A = Zn, Cd, Hg; X = S, Se) 19,20 . In particular, we have shown that the ratio of the next-nearest neighbor (K nnn ) over the nearest neighbor (J nn ) magnetic interactions is proportional to the structural transition pressure (P Tr ) from the starting cubic Fd3 m phase towards a tetragonal modification 21,22 .…”
Section: Fig 1 the Crystal Structure Of The A 2+ Cr 3+mentioning
confidence: 93%
See 1 more Smart Citation